Wound Healing in a Bitch with Topical use of Cannabis Oil - Mariga, Carollina; Teixeira, Bruna Antunes; Lemos Pinto Filho, Saulo Tadeu (Acta Scientiae Veterinariae, 2024)
Background: The presence of the endocannabinoid system (ECS) in the skin is unique, and the complexity among receptors, cannabinoids, enzymes, and cells involved results in various processes encompassing this microenvironment. The ECS involves CB1 and CB2 receptors in keratinocytes, nerve fibers, dermal cells, melanocytes, sweat glands, and hair follicles. This intricate interaction represents a therapeutic potential still scarce in veterinary medicine. Therefore, this study aims to report the topical use of Cannabis oil to aid in the healing of a surgical wound that presented suture dehiscence in the postoperative period. Case: A 6-year-old not spayed bitch Great Dane experienced suture dehiscence after undergoing surgical excision. The owner reported local discomfort with pain and itching, leading to difficulty in wound care. A full-spectrum Cannabis oil rich in cannabidiol (CBD) was prescribed, with instructions for local application on the wound edges and directly on the lesion twice daily until resolution. The owner reported clinical improvement after the 1st application, applying only once daily for the remainder of the treatment. The animal exhibited accelerated healing, and the owner was satisfied with the ease of wound care, concluding the treatment in 7 days. Discussion: The involvement of the ECS with TRPV, TRPA, TRPM, GPR, GlyR, and adenosine (A2A) receptors located in various skin cell types results in functions such as maintaining the cutaneous barrier, cellular growth and differentiation, and immune and inflammatory processes. It has also been associated with the imbalance of the ECS contributing significantly to skin injuries, including the link between wounds and pain. CBD can increase adenosine signalling, resulting in anti-inflammatory effects, along with the ability to interact with other nuclear and vanilloid receptors with analgesic and anti-itch effects, thus acting in the initial phase of healing, transitioning to a less intense phase, and accelerating the overall process. The ECS is not only present extracellularly but also involves intracellular interactions through nuclear receptors and signalling pathways, allowing for epigenetic modulation to promote analgesia and healing. Some studies have shown that the presence of CBD leads to negative regulation of genes involved in healing and inflammation. CB2 receptor agonists in the wound microenvironment improve local unregulated inflammation through pro-inflammatory cytokines and transforming pro-inflammatory macrophages into anti-inflammatory ones. Additionally, in chronic wounds, the anti-inflammatory properties inhibit the proliferation of hyperproliferative keratinocytes. The topical application of phytocannabinoids and the reduction of the animal’s local discomfort can be explained through the presence of CB1 and CB2 cannabinoid eceptors in skin nerve fibers, decreasing their excitation and, consequently, itching. Skin homeostasis is intrinsically linked to the ECS through the regulation of various aspects of cell proliferation, differentiation, and inflammatory signalling. Despite limited publications, evidence suggests that the topical application of cannabinoids is effective in cutaneous disorders, including chronic or acute wounds. It can be concluded that the treatment with full-spectrum Cannabis oil rich in CBD applied topically has proven to be a good therapeutic option in cases of surgical wound dehiscence in dogs and has high therapeutic potential in chronic and/or complicated diseases. Keywords: Cannabis, cannabidiol, wound, inflammation, canine, skin, regeneration. Título: Cicatrização de ferida em uma cadela com uso tópico de óleo de Cannabis Descritores: Cannabis, canabidiol, ferida, inflamação, canino, pele, regeneração.